النظام القانوني للتنازل عن الأملاك العقارية التابعة للدولة ودواوين الترقية والتسيير العقاري - بن شعبان، علي (جامعة ابن خلدون تيارت, 2017)
In order to regulate the situation of the real estate of the private state domines and public property of the state as well as its local communities and the public institutions like the real estate promotion offices, the Algerian legislator has found some new important solutions, which involve changes in the legal nature of real estate by passing from a public fund a private property, by the sharing and desistance of property in favor of the beneficiaries whether they are residential premise, commercial, professional or artisanal.
في إطار تسوية وضعية الأملاك العقارية الخاصة والعمومية التابعة للدولة وجماعاتها المحلية ولدواوين الترقية والتسيير العقاري، استحدث المشرع الجزائري بعض الحلول الجديدة والهامة التي من شأنها تغيير في الطبيعة القانونية للأملاك العقارية من ملكية عامة إلى ملكية خاصة بعد التنازل عنها للخواص، سواء تعلق الأمر بالتنازل عن الأملاك العقارية ذات الطابع السكني أو المهني أو التجاري أو الحرفي أو الوظيفي التابعة للدولة ودواوين الترقية والتسيير العقاري.
Keywords: التنظيمات القانونية -- الأملاك العقارية -- التسيير العقاري -- التنمية المستدامة -- التشريعات الجزائرية